Isolation of Clostridium perfringens from chickens and detection of the alpha toxin gene by polymerase chain reaction (PCR) - Kalender, H; Ertas, HB (Tubitak Scientific & Technological Research Council Turkey, 2005)
This study was carried out to isolate Clostridium perfringens from chickens and to detect the gene encoding the alpha toxin produced by all types of C. perfringens by polymerase chain reaction (PCR). Intestinal contents of 160 slaughtered chickens from 8 different farms in Elazig province were analyzed. C. perfringens was isolated from 8 (5%) of the samples. DNA samples extracted from suspected isolates grown on selective agar were amplified by PCR using a pair of primers derived from the alpha toxin gene. All of 8 suspected isolates were, found to be C. perfringens by conventional methods and PCR. Isolates were typed by the toxin neutralization test. Of the 8 isolates, 6 were type A and 2 could not be typed. Since C. perfringens type A is associated with food poisoning in humans, the isolation of C. perfringens type A from chickens in this study is important for public health.
Keywords: chicken; Clostridium perfringens; isolation; PCR; alpha toxin